The immunogenicity of Eimeria tenella sporozoite proteins and living oocyst vaccines in broilers Imunogenicidade de vacina com proteínas de esporozoítos e oocistos vivos de Eimeria tenella em frangos - Odilon Vidotto (Semina: Ciências Agrárias, 2012)
The purpose of the present study was to evaluate the immunity of broilers inoculated with sporulated oocysts and sporozoite proteins of Eimeria tenella against challenge with homologous infectives oocysts. Broiler chickens of Hubbard strain, females, coccidian-free, were kept in wire cages and inoculated on the third day (day 0). Three treatments were used: T1, the negative control; T2, received 500 sporulated oocysts by gavage; T3, positive control; T4, received 50 ?g of sporozoite protein with Quil A; and T5, received Quil A without sporozoite protein and PBS, the last two protocols were administered via nasal route on days 0, 7, and 21. On the 31st day, all groups, with the exception of T1, were challenged with homologous virulent strain of E. tenella at the dose of 8.0×104 oocysts. Immunogenicity was assessed by carotenoids, ELISA assay, histopathological analysis, oocysts count and lesion score. Antibody kinetics were measured weekly and showed a gradual increase in levels of immunoglobulin for treatment T2 and T4, reaching a peak on day 21. Based on the parameters evaluated, a total protecting immunological effect for the infectant oocysts vaccine (T2) and partial protection for the sporozoite protein vaccine (T4) against homologous virulent strain challenge were observed. O objetivo do presente estudo foi avaliar a imunidade de frangos de corte inoculados com oocistos esporulados e proteínas de esporozoítos de Eimeria tenella utilizando um desafio com oocistos esporulados homólogos. Frangos de corte da linhagem Hubbard, fêmeas, livres de coccidiose, foram mantidos em gaiolas de arame e inoculados no terceiro dia (dia 0). O delineamento experimental consistiu de cinco tratamentos com três repetições: T1- controle negativo; T2- recebeu 500 oocistos esporulados por gavagem; T3- controle positivo; T4- receberam 50 ?g de proteína de esporozoítos adicionados a Quil-A, e finalmente o T5- que recebeu apenas Quil A e PBS, os últimos dois protocolos foram administrados pela via nasal nos dias 0, 7 e 21. No dia 31, todos os grupos, com exceção do T1, foram desafiados com uma cepa homóloga virulenta de E. tenella na dose de 8,0 × 104 oocistos esporulados. A imunogenicidade foi avaliada por níveis de carotenóides, ELISA, análise histopatológica, contagem de oocistos e índice de lesões. Com base nos parâmetros avaliados, a vacina de oocistos infectante (T2) mostrou uma proteção total e a vacina de proteína de esporozoítos (T4) uma protecção parcial contra o desafio homólogo com cepa virulenta.